2019
DOI: 10.1111/nph.15786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host phylogeny, habitat and spatial proximity on host specificity and diversity of pathogenic and mycorrhizal fungi in a subtropical forest

Abstract: Summary Soil plant‐pathogenic (PF) and mycorrhizal fungi (MF) are both important in maintaining plant diversity, for example via host‐specialized effects. However, empirical knowledge on the degree of host specificity and possible factors affecting the fungal assemblages is lacking. We identified PF and MF in fine roots of 519 individuals across 45 subtropical tree species in southern China in order to quantify the importance of host phylogeny (including via its effects on functional traits), habitat and spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 86 publications
9
69
0
Order By: Relevance
“…Furthermore, the endophytic fungal OTU richness was affected by host phylogeny, geographic distance, MAT and soil total N. Similar results were reported in previous studies on rootassociated fungal communities, such as EM fungi (Tedersoo et al, 2013;Wu et al, 2018;Wang et al, 2019a), AM fungi (Davison et al, 2015;Van Geel et al, 2018) and pathogenic fungi (Wang et al, 2019b). We found that host phylogeny significantly shaped endophytic fungal community composition.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Furthermore, the endophytic fungal OTU richness was affected by host phylogeny, geographic distance, MAT and soil total N. Similar results were reported in previous studies on rootassociated fungal communities, such as EM fungi (Tedersoo et al, 2013;Wu et al, 2018;Wang et al, 2019a), AM fungi (Davison et al, 2015;Van Geel et al, 2018) and pathogenic fungi (Wang et al, 2019b). We found that host phylogeny significantly shaped endophytic fungal community composition.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to environmental filtering by host plants, abiotic environmental variables including soil (pH, nutrients, and particle size distribution) and climate (MAT and MAP) have also been observed to affect endophytic fungal community in this study. Similar findings were also reported in some studies on root-associated fungal communities, such as endophytic fungi (Maciá-Vicente et al, 2012;Glynou et al, 2016), EM fungi (Jarvis et al, 2013;Miyamoto et al, 2015;Wang et al, 2019a), AM fungi (Dumbrell et al, 2010;Zheng et al, 2014;Van Geel et al, 2018), pathogenic fungi (Wang et al, 2019b), and total fungi (Barnes et al, 2018;Li et al, 2018). Fungal taxa are known to prefer to FIGURE 5 | Result of variation partitioning analysis showing pure and shared effects of plant, soil, climatic and spatial variables on endophytic fungal community composition.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations